2013
DOI: 10.3727/108354213x13782245307911
|View full text |Cite
|
Sign up to set email alerts
|

Do Political Instability, Terrorism, and Corruption Have Deterring Effects on Tourism Development Even in the Presence of Unesco Heritage? A Cross-Country Panel Estimate

Abstract: This article evaluates the effects of political instability, terrorism, and corruption on tourism development, particularly UNESCO-listed heritage destinations. Using a fixed-effects panel data analysis for 139 countries over the period 1999–2009, the result reveals that a one-unit increase in political instability decreases tourist arrivals and tourism revenue between 24% and 31% and 30% and 36%, respectively. Furthermore, in the presence of heritage, terrorism has negative effects on tourism demand even tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
119
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(141 citation statements)
references
References 26 publications
(36 reference statements)
13
119
0
7
Order By: Relevance
“…The study further explains that the marginal gain in tourism competitiveness from a reduction in corruption levels is greater for developing countries than for developed countries. On the other hand, Yap and Saha () found that an increase in corruption would not have an adverse effect on tourism demand for destinations that have historical and natural heritage. They argued that most travellers are expected to pay bribes for visas or permits when travelling to these destinations.…”
Section: The Effects Of Corruption On Tourism: a Brief Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The study further explains that the marginal gain in tourism competitiveness from a reduction in corruption levels is greater for developing countries than for developed countries. On the other hand, Yap and Saha () found that an increase in corruption would not have an adverse effect on tourism demand for destinations that have historical and natural heritage. They argued that most travellers are expected to pay bribes for visas or permits when travelling to these destinations.…”
Section: The Effects Of Corruption On Tourism: a Brief Literature Reviewmentioning
confidence: 99%
“…Following the methodology suggested by Saha and Gounder () and Yap and Saha (), we begin our analysis by focusing on the conventional linear functional form. The linear base model is presented as follows: leftTDitalicit=β0+β1CORRitalicit+β2logRGDPPCitalicit+β3IEXCi+β4CEXCitalicit+β5logATTitalicit+β6H+β7N+εitalicitwhere TD is tourism demand, i is country, t is time, RGDPPC is real gross domestic product per capita, IEXC is the initial exchange rate (based on exchange rates in the year 1999), CEXC is changes in exchange rates, ATT is tourist attractions, H is a dummy variable for countries that have historical heritage approved by United Nations Educational, Scientific and Cultural Organization (UNESCO), N is a dummy variable for countries that have natural heritage approved by UNESCO and ε is the error term.…”
Section: Model Specifications and Data Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, low levels of corruption can be beneficial for the tourism industry. Using 139 countries for the period from 1999 to 2009, Yap and Saha () find that corruption might not be so harmful, if a destination has a historical and natural heritage. Recently, Lv and Xu () observe the significant nonlinear relationship between corruption and tourism demand in 62 countries over the period 1998–2011, but the relationship is significant at the 50th and 75th quantiles.…”
Section: Introductionmentioning
confidence: 99%
“…When violence becomes widespread and prolonged, governments in tourist origin countries will advise against travelling to those destinations and commercial operators will cancel tours because of insufficient bookings and for fear of liability suits, and will promote other destinations instead (Neumayer, 2004). A further problem is that terrorist attacks and political disruption can damage infrastructure relevant to the tourism industry (Llorca-Vivero, 2008) and may damage or destroy national treasures (Yap & Saha, 2013).…”
Section: Special Issue On Tourism and Instabilitymentioning
confidence: 99%